Integrative genetic analysis reveals shared genetic architecture underlying coronary artery disease, CT-Defined coronary atherosclerosis, and cardiometabolic risk factors - Yao Zhao; Yingying Xie; Didi Wen; Jin Zhang; Ziliang Xu; Zhibin Wu; Jiaming Li; Yuanqiang Zhu; Minwen Zheng (Functional & Integrative Genomics, 2026)

LARIS: a local-state active reasoning and integrated switching framework for robotic harvesting under partial observability - Nianzu Dai; Jiaming Fang; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

3D laser scanning-based geometry reconstruction and stress evaluation of a KK-type cast steel node for offshore wind turbine jacket structures - Feng Shi; Hui Jin; Lu Xu; Jiaming Liu; Jiahao Hu; Haihan Jiao (Ocean Engineering, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Multi-omics analysis revealed promoting mechanism of gut derived cellulose-degrading bacteria from Tenebrio molitor on bioconversion of lignocellulosic waste - Xinrui Mao; Wenbiao Jin; Jiaming Li (Bioresource Technology Reports, 2026)

High turbidity induced by extreme precipitation complicates the relationships between molecular and optical properties of DOM in the Yangtze River - Yue Ren; Guangrui Yang; Jiale Jin; Chu Zhao; Zhishan Ye; Jiaming Chen; Xinyi Zhang; Tao Huang; Changchun Huang (Journal of Water Process Engineering, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Localized chemotherapy through metabolic stabilization and in situ gelation for ratio-locked delivery to maximize cytotoxicity and trigger immune responses - Jiaming Zhang; Xinyu Lou; Xiaolan Xu; Yingchao Li; Chenxia Bai; Qing Yan; Yanfang Wang; Yixiu Zhai; Jingdong Xiao; Mengchi Sun; Yinghou Wang; Jin Sun; et al. (Chemical Engineering Journal, 2026)

Design of a green certificate differentiated issuance mechanism based on renewable energy enterprises subsidy perspective: A case study of China - Qinliang Tan; Chaofan Shi; Jiabin Zeng; Zihan Jin; Yihong Ding; Jiaming He; Guangyu Qin (Energy Policy, 2026)

Pipeline Systems in Floating Offshore Production Systems: Hydrodynamics, Corrosion, Design and Maintenance - Jin Yan; Yining Zhang; Zehan Chen; Pengji Li; Yuting Li; Zeyu Cao; Jiaming Wu; Kefan Yang; Dapeng Zhang (Journal of Marine Science and Engineering, 2026)
Floating offshore production systems play a critical role in offshore resource development, where the structural integrity and operational safety of risers, umbilical cables, and mooring cables are of paramount importance. Focusing on the failure risks of these key components under harsh marine environments, this paper systematically reviews the coupled mechanisms of wave-induced loading, electrochemical corrosion, and material fatigue. Unlike traditional reviews on offshore pipelines and cables, this study not only examines the mechanical performance of deepwater pipelines and cables along with representative research cases but also discusses corrosion mechanisms in marine environments and corresponding repair and mitigation strategies. In addition, recent advances in machine learning-based digital twin frameworks and real-time monitoring technologies are reviewed, with an analysis of representative application cases. The findings indicate that interdisciplinary material innovations combined with data-driven predictive models are essential for addressing maintenance challenges under extreme ocean conditions. Furthermore, this review identifies existing research gaps in data fusion for monitoring technologies and outlines clear directions for the intelligent operation and maintenance of future deep-sea infrastructure.

Reshaping spatial–temporal pattern of suspended sediment concentration in the Yangtze River mainstem by damming reservoirs based on nearly 40 years Landsat observations - Farong Chen; Guangrui Yang; Yanhui Dai; Jiale Jin; Chu Zhao; Zhishan Ye; Jiaming Chen; Xinyi Zhang; Tao Huang; Changchun Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Thermostatic nucleic acid amplification technology in foodborne pathogen detection: opportunities and challenges - Moran Zhang; Jiaming Huang; Yongjin Dai; Shanshan Jin; Qianqian Jia; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (Critical Reviews in Food Science and Nutrition, 2025)

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

An in-situ generated multiphase catalyst for active and durable ammonia protonic ceramic fuel cells - Haiyang Lan; Zixuan Xue; Jiakun Sun; Jiaming Chu; Jiangyuan Feng; Weitao Jin; Zixian Wang; Ruiqing Song; Pengfei Yan; Liang Zhang; Yucun Zhou; Xiaofeng Ye; et al. (Chemical Engineering Journal, 2025)

Integrated multi-omics reveals mechanistic impact of gut microbiota inhibition on lignocellulose biodegradation in Tenebrio molitor - Xinrui Mao; Jiaming Li; Wenbiao Jin; Wei Han (Bioresource Technology, 2025)

Br− as a potential suppressor of NDMA formation during ozonation of HDMS: Mechanisms and implications - Fan Zhou; Menglan Gao; Xiaobin Liao; Jiaming Zhu; Zhenkun Chen; Huatong Ma; Huayu Zhang; Jin Wang; Chenyang Liao; Mingzhi Huang; Zhimin Yang (Chemical Engineering Journal, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Study on hot spot stress distribution and fatigue life assessment of KK-type cast steel nodes based on scaled model test - Haihan Jiao; Jiaming Liu; Lu Xu; Feng Shi; Hui Jin; Yongchun Fan (Ocean Engineering, 2025)

Oxidation mechanisms of ammonia and ethanol mixed fuel by using the ReaxFF-MD simulation - Chongchong She; Chunchen Xu; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

Unmet needs of patients with intravascular large B-cell lymphoma: three case reports and a literature review - Xian Li; Ru Luo; Jiaming Xu; Xueli Jin; Weiqin Wang; Xibin Xiao; Wenbin Qian (Journal of Zhejiang University-SCIENCE B, 2025)

Design and interaction dynamics analysis of a novel hybrid bending-twisting-pulling end-effector for robotic tomato picking - Jiaming Fang; Nianzu Dai; Zhenbo Xin; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Multi-omics revealed activation of TNF-α induced apoptosis signaling pathway in testis of DEHP treated prepubertal male rat - Zishui Fang; Zirun Jin; Qiancheng Zhao; Jiaming Weng; Zhe Zhang; Yuzhuo Yang; Hui Jiang (Reproductive Toxicology, 2025)

Insights into the combustion mechanisms of turpentine oil based on ReaxFF molecular dynamics simulations - Chongchong She; Tiancheng Zhang; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

3MSP2: Sequential picking planning for multi-fruit congregated tomato harvesting in multi-clusters environment based on multi-views - Nianzu Dai; Jiaming Fang; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2024)

Boosting charge transfer promotes photocatalytic peroxymonosulfate activation of S-doped CuBi2O4 nanorods for ciprofloxacin degradation: Key role of Ov–Cu–S and mechanism insight - Xianzhong Bu; Jiaming Li; Jin Wang; Yuan Li; Gaoke Zhang (Chemical Engineering Journal, 2024)

Cryopreserved leukapheresis material can be transferred from controlled rate freezers to ultracold storage at warmer temperatures without affecting downstream CAR-T cell culture performance and in-vitro functionality - Jiaming Wei; Katherine Chaney; Woo Jin Shim; Heyu Chen; Grace Leonard; Sean O'Brien; Ziyan Liu; Jinlin Jiang; Robert Ulrey (Cryobiology, 2024)

Responses of physiological, microbiome and lipid metabolism to lignocellulose wastes in gut of yellow mealworm (Tenebrio molitor) - Xinrui Mao; Jiaming Li; Enqing Meng; Wenbiao Jin; Wei Han (Bioresource Technology, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

A new strategy for self-bio-driven granular sludge in a continuous-flow reactor: Applying spherical pelletizing granular sludge as a nucleus - Zhuo Sun; Libin Zhang; Xuejiao Huang; Zhongqin Jiang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Jiaming Zhang; Dandan Jia (Journal of Cleaner Production, 2024)

Effects of dietary vitamin E supplementation on growth performance, slaughter performance, antioxidant capacity and meat quality characteristics of finishing bulls - Jiaming Luan; Yinghai Jin; Tai Zhang; Xin Feng; Kai Geng; Min Zhang; Chunyin Geng (Meat Science, 2023)

The carbon reduction effects of stepped carbon emissions trading and carbon capture and storage on hybrid wind-PV-thermal- storage generation operating systems - Yongmei Wei; Xinyu Wang; Jin Zheng; Yihong Ding; Jiaming He; Jian Han (Environmental Science and Pollution Research, 2023)

Four new terpenoids and other metabolites with potential anti-complementary activities from the aerial parts of Dracocephalum moldavica (Lamiaceae) - Jiaming Wang; Jinfeng Sun; Long Jin; Yanyan Huang; Mengjie Wang; Mei Jin; Shengbao Diao; Wei Zhou; Gao Li (Natural Product Research, 2023)

Detection and characterization of microplastics in the human testis and semen - Qiancheng Zhao; Long Zhu; Jiaming Weng; Zirun Jin; Yalei Cao; Hui Jiang; Zhe Zhang (Science of The Total Environment, 2023)

In-depth understanding of catalytic and adsorbing effects in polysulfides conversion and rationally designing coaxial nanofibers for Li-S batteries - Jiaming Tian; Zihan Shen; Huiting Cheng; Xin Jin; Zhonghua Li; Yang Wen; Junfeng Hui; Shaohua Guo; Huigang Zhang; Qingshan Zhu (Chemical Engineering Journal, 2023)

A new monoterpenoid glycoside and a new phenolic glycoside isolated from Dracocephalum moldavica and their anti-complementary activity - Jiaming Wang; Jinfeng Sun; Long Jin; Mengjie Wang; Yanyan Huang; Mei Jin; Wei Zhou; Gao Li (Natural Product Research, 2023)

Direct start-up of aerobic granular sludge system with dewatered sludge granular particles as inoculant - Zhuo Sun; Jiaming Zhang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Guoyou Nong; Mengqi Luo; Jue Wang (Journal of Environmental Management, 2023)

Lack of Knowledge, the main Stumbling Block of Fertility Preservation Promotion in China - Meng Wang; Lixia Zhu; Hua Xiong; Jiaming Wang; Zhou Li; Liu Yang; Lei Jin; Qingsong Xi (Journal of Cancer Education, 2022)

Design, synthesis and biological evaluation of indoline derivatives as multifunctional agents for the treatment of ischemic stroke - Shuaishuai Du; Fan Jin; Jiaming Li; Xiaodong Ma; Hongwei Wang; Shihu Qian (Medicinal Chemistry Research, 2022)

Two new phenolic glycosides with anti-complementary activity from the roots of Sanguisorba officinalis L - Rongshen Wang; Jinfeng Sun; Mei Jin; Chao Ye; Jiaming Wang; Long Jin; Ying Jie Ma; Wei Zhou; Gao Li (Natural Product Research, 2021)

Two novel flavonoids from the leaves of Rhododendron dauricum L. with their inhibition of TNF-α production in LPS-induced RAW 264.7 cells - Chao Ye; Mei Jin; Chunshi Jin; Rongshen Wang; Jiaming Wang; Ying Zhang; Sainan Li; Jinfeng Sun; Wei Zhou; Gao Li (Natural Product Research, 2021)

A new pentacyclic triterpenoid from the leaves of Rhododendron dauricum L. with inhibition of NO production in LPS-induced RAW 264.7 cells - Jiaming Wang; Mei Jin; Chunshi Jin; Chao Ye; Yi Zhou; Rongshen Wang; Huanhuan Cui; Wei Zhou; Gao Li (Natural Product Research, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)

The Arg194Trp polymorphism in the XRCC1 gene and cancer risk in Chinese Mainland population: a meta-analysis - Jin Huang; Jie Zhang; Yuliang Zhao; Banghua Liao; Jiaming Liu; Ling Li; Mingheng Liao; Lanlan Wang (Molecular Biology Reports, 2011)